Knowledge, Attitudes, and Practices on the Prevention of Ventilator-Associated Pneumonia among Nurses in ICU Units at Government Hospitals in Saudi Arabia - Shahad Fahad Albariqi; Maha Jurayed Alharbi; Abeer Mohammed Alrasheedi; Ragdah Saad Alasmary; Mashail Saud Alrashidi; Saleh Salem Alswar; Amnah Mohammed Aldossary; Ali Mohammed Ali Al Bishr; Almotairi, Basema Noor; Alharbi , Khalda Khaled Jahaz (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Nurses working in the ICU require specialized skills and knowledge to provide safe and high-quality care to critically ill patients. Ventilator-Associated Pneumonia (VAP) is a recognized nosocomial infection and a leading cause of high morbidity and mortality. Intensive Care Unit (ICU) nurses are in the best position to assess knowledge, attitude and practices on the prevention of VAP. Objective: The aim of this study was to assess knowledge, attitude and practices on the prevention of VAP among nurses in ICU Units at Government Hospitals in Saudi Arabia. Methods: This study used a cross-sectional and descriptive quantitative design conducted 2024 in ICU Units at Government Hospitals in Saudi Arabia (n = 113; census study). A self-structured questionnaire consists of 4 parts, part 1 included socio-demographic data; part 2: included a scale containing 13 questions to assess the knowledge on prevention of VAP. part 3: included four paragraphs to determine the existing attitude of nurses towards prevention of VAP; part 4: included a checklist to describe practice of nurses on prevention of VAP. Results by using the Statistical package for social sciences (SPSS) the level of knowledge of adult intensive care nurses about the prevention of pneumonia associated with ventilators was moderate (58%); the level of attitudes was moderate (66.4%); and the level of practice was high (74%). The most important practices of nurses to prevent VAP were. Hand washing. About 87.6% of nurses wash their hands before entering the ICU, and 90.3% of them wash their hands before touching the patient, while 69.9% wash hands after touching the patient. As for practices related to Suctioning from the ETT/tracheotomy, 87.6% prepare sterile equipment’s required during suctioning, while 85.0% insert the catheter into the ETT gently by using aseptic technique. Conclusion and Recommendations: The current study shows that nurses had moderate levels of total knowledge and attitudes while practice was high. Therefore, Hospital’s administrations in collaboration with continuous education committee should focus on establishing educational programs and protocols to prevent and reduce the incidence of VAP and to enhance nurses’ knowledge on prevention of VAP.